(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kolbakova T. S. Forming of professional consciousness of future teachers in the process of professional training at higher schools of the firstt and the second accreditation levels. The article discusses issues concerning developing professional consciousness of future teachers in the process of their professional training at universities of the first and the second accreditation levels. The author describes the idea of professional consciousness and its components. She also defines features of professionally important characteristics of professional consciousness of future teachers.